M2 microglia-derived exosomes reduce neuronal ferroptosis via FUNDC1-mediated mitophagy by activating AMPK/ULK1 signaling - Jian Li; Qing Chen; Hao Gu (Scientific Reports)
Abstract Neuronal ferroptosis plays a vital role in the progression of neonatal hypoxic-ischemic brain damage (HIBD). M2-type microglia-derived exosomes (M2-exos) have been shown to protect neurons from ischemia–reperfusion (I/R) brain injury, but their impact on I/R-induced neuronal ferroptosis and the underlying mechanisms remain poorly understood. In this study, we used an in vitro oxygen-glucose deprivation/reoxygenation (OGD/R) model in HT-22 neuronal cells to investigate how M2-exos modulate ferroptosis. We found that M2-exos were internalized by HT-22 cells and significantly attenuated OGD/R-induced ferroptosis. Mechanistically, M2-exos enhanced mitophagy, which was mediated by the upregulation of FUN14 domain-containing protein 1 (FUNDC1), thereby inhibiting ferroptosis. Further analysis revealed that M2-exos activated FUNDC1-dependent mitophagy through the AMP-activated protein kinase (AMPK)/UNC-51-like kinase 1 (ULK1) signaling pathway. Taken together, these findings suggest that M2-exos ameliorate I/R-induced neuronal ferroptosis by enhancing FUNDC1-mediated mitophagy through the activation of AMPK/ULK1 signaling pathway.